Integrated sustainability assessment: what is it, why do it and how?. (24th May 2007) - Weaver, Paul M.; Rotmans, Jan
This paper describes a new conceptualisation of sustainability assessment as an integrative and active process at the science-policy-society interface and its implementation as exemplified in case studies within the Methods and Tools for Integrated Sustainability Assessment (MATISSE) project. Integrated Sustainability Assessment (ISA) is defined within the MATISSE project as a cyclical, participatory process of scoping, envisioning, experimenting and learning through which a shared interpretation of sustainability for a specific context is developed and applied in an integrated manner in order to explore solutions to persistent problems. ISA is strategic, sustainability-oriented, constructive and potentially transformative. Its key role is to explore the opportunity-creation and problem-solving potential of framing contexts other than those in place, such as alternative institutions, technologies, spatial and temporal arrangements, price relations and associated policy regimes.